Self-assembly of silica particles in a nonionic surfactant hexagonal mesophase - Sharma, Kamendra P.; Kumaraswamy, Guruswamy; Ly, Isabelle; Mondain-Monval, Olivier (Journal of Physical Chemistry B, 2009)
We investigate the process of self-assembly, and the resultant structures in composites of silica particles with a hexagonal mesophase of a nonionic surfactant and water. We report a systematic transition in behavior when the particle size is increased relative to the characteristic mesophase spacing. Water dispersible cage-like silsesquioxanes that are molecular analogues of silica particles and are smaller than the mesophase spacing swell the space between the surfactant cylinders. Silica particles comparable to the characteristic hexagonal spacing partition into the hexagonal phase and into strandlike particulate aggregates. Even larger particles phase separate from the hexagonal phase to form particulate strands that organize with a mesh size comparable to the wavelength of visible light. This self-assembly is reversible and the particles disperse by breaking up the aggregates on heating the composite into the isotropic phase. On cooling from the isotropic phase into the hexagonal, the particles are expelled from the growing hexagonal domains and finally impinge to form strandlike aggregates. Unusually, the isotropization temperature is increased in the composites as the particles nucleate the formation of the hexagonal phase.

Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.